Procalcitonin Test in Rheumatologist's Practice - N. V. Muravyeva; B. S. Belov; G. M. Tarasova (Антибиотики и Химиотерапия, 2020)
The aim of the work is to evaluate the diagnostic significance of the procalcitonin test (PCT) in the practice of a rheumatologist.Material and methods. The study included 360 patients with various immuno-inflammatory rheumatic diseases (IIRD). Serum PCT concentration was determined by a quantitative electrochemiluminescent method on a Cobas E 411 analyzer (Roshe, Switzerland).Results. The median (Me) level of PCT was 0.11 ng/ml [0.05; 0.16] in patients without infection (n=191). In patients with generalized infection (n=11), the Me level of PCT was 3.6 ng/ml [0.88; 11.3]. In cases of severe local infection (n=75), the Me level of PCT was 0.45 ng/ml [0.24; 1,2], while in case of mild local infection (n=83) — 0.12 ng/ml [0.05; 0.17]. ROC curve analysis showed that the diagnostic significance of determining PCT for generalized infection is very high, for severe local infection it is high, and for differentiation of generalized infection from local infection it is high.Conclusion. PCT is a valuable diagnostic test that helps recognize generalized and severe local infections in patients with IIRD. However, when interpreting the values of PCT, the totality of data should be taken into account: specific rheumatic nosology, results of clinical laboratory, and instrumental examinations.